Analisis Fungsi Taman-Taman Kota di Kota Bogor Berdasarkan Persepsi Masyarakat - Astiandi, Satria; Hidayah, Ulul (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
The availability of city parks is an important thing in spatial planning. This is regulated in the Ministerial Regulation (Permen) of Public Works (PU) Number 05/PRT/M/2008. Referring to this policy, the number of city parks in Bogor City has met the minimum requirements. However, more than quantity is needed if it is balanced with good quality city parks. This research aims to identify the quality of city park functions in Bogor City based on public perceptions. This research is descriptive with an inductive analysis method. Data was collected from part of the population using a random sampling method. Based on the analysis of the four functions of parks in Bogor City, they are running relatively well. Ecologically, city parks in Bogor, on average, have a good function as noise reducers, oxygen producers, windbreaks, and rain catchment areas. Regarding social and cultural functions, city parks in Bogor City have various assessments. People give a good assessment of the function of city parks as a means of social interaction, recreation, and play. Economically, city parks in the city of Bogor are considered by the community to be a sufficient space for economic interaction. However, no source of products produced from these city parks can have economic value. Aesthetically, city parks in Bogor City have a good average score for their function as supporting the city's beauty, increasing comfort, and forming factors of architectural beauty. It is hoped that the findings from this research can become a basis for improving the arrangement and management of city parks in Bogor City.